Ultrasensitive Nanosensors Based on Upconversion Nanoparticles for Selective Hypoxia Imaging in Vivo upon Near-Infrared Excitation - Liu, Jianan; Liu, Yong; Bu, Wenbo; Bu, Jiwen; Sun, Yong; Du, Jiulin; Shi, Jianlin (Journal of the American Chemical Society, 2014)
Hypoxia is a distinct feature of malignant solid tumors, which is a possible causative factor for the serious resistance to chemo- and radiotherapy or the development of invasion and metastasis. The exploration of nanosensors with the capabilities like the accurate diagnosis of hypoxic level will be helpful to estimate the malignant degree of tumor and subsequently implement more effective personalized treatment. Here, we report the design and synthesis of nanosensors that can selectively and reversibly detect the level of hypoxia both in vitro and in vivo. The designed nanosensor is composed of two main moieties: oxygen indicator [Ru(dpp)3]2+Cl2 for detection of hypoxia and upconversion nanoparticles for offering the excitation light of [Ru(dpp)3]2+Cl2 by upconversion process under 980 nm exposure. The results show that the nanosensors can reversibly become quenched or luminescent under hyperoxic or hypoxic conditions, respectively. Compared with free [Ru(dpp)3]2+Cl2, the designed nanosensors exhibit enhanced sensitivity for the detection of oxygen in hypoxic regions. More attractively, the nanosensors can image hypoxic regions with high penetration depth because the absorption and emission wavelength are within the NIR and far-red region, respectively. Most importantly, nanosensors display a high selectivity for detection of relevant oxygen changes in cells and zebrafish.